Montesquieu - Larrère, Catherine (1996)
Montesquieu (1996) 3 juin 2012, par Larrère, Catherine dans Dictionnaire de philosophie politique, éd. Stéphane Rials et Philippe Raynaud, Paris, PUF, 1996, p.400-407.
Keywords: exportSPIP